Evaluasi Web Sistem Informasi Pemerintahan Daerah (SIPD) Bappelitbangda Mempergunakan Metode System Usability Scale - Hernafa Annaasthasya Suryanto; Resad Setyadi (STMIK Budi Darma, 2022)
Bappelitbangda (Development Planning, Research and Development Agency) is a government agency that has the task of assisting the Regent in implementing regional government. Bappelitbanda has several systems that are used to support work performance, one of which is the SIPD website system, one of these systems functions to be able to assist community reporting regarding regional development. On the website system, various obstacles are often encountered, one of which is accessing or logging in to the intended menu which is very complicated, the display does not match. Therefore, this study aims to evaluate the usability related to the SIPD website system using the System Usability Scale (SUS) evaluation method. Using this method is useful for assessing a system regarding usability. The data obtained from this study by distributing questionnaires found 20 respondents. The results of calculating the average score based on the SUS method are 34.20454545, which means that the system is declared Not Acceptable with a low position included in the F scale grade with poor branches, so it can be concluded that the use of the system cannot be fully used easily by system users, users still experience difficulties in using the SIPD system.